Call Me Bathsheba: A Novel Exploring the Impacts of Patriarchal Culture on the Prostitution Industry - Joana Joana; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2021)
This creative work follows the journey of the daughter of a prostitute, in her attempt to survive after being kicked out of the house and find the biological mother whom she never met. It explores the theme of patriarchal culture that impacts prostitution industry and the complication of it.This realistic fiction novel was set in three countries which are China (Hong-Kong), Singapore, and Indonesia. The story highlights the reasons women enter prostitution explored in Barry’s The Prostitution of Sexuality theory, and the physical and pyscho-social impacts of slut-shaming happened to women prostitute explored in Benoit et al’s Theory of Social Stigma among Prostitutes.It will also be elaborated on how patriarchy impacts both issues. Through these theories and project, I find that patriachy causes many women decided to enter prostitution as it’s the best choice they have at hand even though the work itself oftentime harms them physically and pyscho-socially through the whore-stigma that operates on the micro, meso, and macro level of their lives. Keywords: patriarchal culture, women prostitution, whore-stigma, slut-shaming.